Arcoiris santiaguinos. Escritos de nómades urbanos. - Figueroa, Gricelda (Confluencia: Revista Hispánica de Cultura y Literatura)
The article presents a critical analysis of urban graffiti in Santiago, Chile. The author provides a history of hip hop graffiti, detailing its origins in the U.S. and Europe. The various styles of graffiti are examined, including wild style and tagging, along with themes and connections to the hip hop culture and lifestyle. Graffiti artists are portrayed as urban nomads and their work is reviewed as street art.